The effect of Adey and Shayer model on achievement and habits of mind among fourth-grade students in physics - Azhar Burhan Ismael (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to identify)) the effect of Adey and Shire's model on achievement and habits of mind among students of the fourth scientific grade in the subject of physics (( and the experimental design was chosen with the two equivalent experimental and control groups with a post-test . To raise Rusafa first . The research sample was determined by random selection of two branches out of the four divisions, one representing the experimental group and the other the control group. The two research tools were represented by using an achievement test of the type of objective questions consisting of 40Paragraph and Scale of Habits of Mind represented by(32)Paragraph spread evenly across(8)fields , The results showed a statistically significant difference at a significant level 0.05For the benefit of the following experimental group students who studied according to the Eddy and Shire model and their superiority over the control group students who studied according to the usual method of achievement and habits of mind Eddy and. According to the research findings, a set of recommendations and proposals were developed Eddy and.